Evaluating and Correcting Inherent Bias of microRNA Expression in Illumina Sequencing Analysis - Baroin-Tourancheau, Anne; Jaszczyszyn, Yan; Benigni, Xavier; Amar, Laurence (Frontiers in Molecular Biosciences, 2019)
microRNA (miRNA) expression profiles based on the highly resolutive Illumina sequencing technology rely on the construction of cDNA libraries in which adaptor ligation is known to deeply favoured some miRNA species over others. This introduces erroneous measurements of miRNA relative quantities and identification of most abundant miRNAs in biological samples. Here, by using the miRXplore commercial sample that contains an equimolar mixture of 963 animal miRNAs and TruSeq adaptors, we describe a method for correcting ligation biases in expression profiles obtained with standard protocols of cDNA library construction and provide data for quantifying true miRNA abundance in biological samples. Here we have evaluated ligation bias at three ratios of miRNA to 3'-adaptor and four numbers of polymerase chain reaction (PCR) amplification cycles by calculating efficiency captures/correcting factors for each miRNA in each case. We show that ligation biases lead to over- or under-expression covering an interval of 105 amplitude. Moreover, at a given miRNA:3'-adaptor ratio, correcting factors of miRNAs of high and low expression in profiles are differently impacted by the number of amplification cycles. Importantly, at a given number of amplification cycles, correcting factors of miRNAs of high and low expression are not impacted by the miRNA:3'-adaptor ratio. Finally we provide tables of correcting factors that allow to measure miRNA abundances in biological samples from TruSeq-based miRNA expression profiles as evidenced by the characterization of miRNAs of the let-7, miR-26, miR-29, miR-30 families as the more abundant miRNAs of the rat adult cerebellum